SARS-CoV-2 Nsp13 encodes for an HLA-E-stabilizing peptide that abrogates inhibition of NKG2A-expressing NK cells - Hammer, Quirin; Dunst, Josefine; Christ, Wanda; Picarazzi, Francesca; Wendorff, Mareike; Momayyezi, Pouria; Huhn, Oisín; Netskar, Herman K.; Maleki, Kimia T.; García, Marina; Sekine, Takuya; Sohlberg, Ebba; et al. (Cell reports (Cambridge), 2022)
Natural killer (NK) cells are innate immune cells that contribute to host defense against virus infections. NK cells respond to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in vitro and are activated in patients with acute coronavirus disease 2019 (COVID-19). However, by which mechanisms NK cells detect SARS-CoV-2-infected cells remains largely unknown. Here, we show that the Non-structural protein 13 of SARS-CoV-2 encodes for a peptide that is presented by human leukocyte antigen E (HLA-E). In contrast with self-peptides, the viral peptide prevents binding of HLA-E to the inhibitory receptor NKG2A, thereby rendering target cells susceptible to NK cell attack. In line with these observations, NKG2A-expressing NK cells are particularly activated in patients with COVID-19 and proficiently limit SARS-CoV-2 replication in infected lung epithelial cells in vitro. Thus, these data suggest that a viral peptide presented by HLA-E abrogates inhibition of NKG2A+ NK cells, resulting in missing self-recognition. [Display omitted] •SARS-CoV-2 Non-structural protein 13 encodes for an HLA-E-restricted peptide•HLA-E/Nsp13232–240 complexes do not bind to the inhibitory receptor NKG2A•Nsp13232–240 allows for NKG2A+ NK cell activation by missing self-recognition•NKG2A+ NK cells proficiently restrict SARS-CoV-2 replication in vitro Natural killer (NK) cells eliminate virus-infected cells. Hammer et al. show that SARS-CoV-2 encodes for a peptide that does not bind to an inhibitory receptor of NK cells, thereby facilitating NK cell activation. This missing self-recognition could enable NK cells to detect and kill SARS-CoV-2-infected cells.